2016
DOI: 10.3389/fmicb.2016.00566
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Secondary Metabolites in Cereals: Potential Involvement in Resistance to Fusarium and Mycotoxin Accumulation

Abstract: Gibberella and Fusarium Ear Rot and Fusarium Head Blight are major diseases affecting European cereals. These diseases are mainly caused by fungi of the Fusarium genus, primarily Fusarium graminearum and Fusarium verticillioides. These Fusarium species pose a serious threat to food safety because of their ability to produce a wide range of mycotoxins, including type B trichothecenes and fumonisins. Many factors such as environmental, agronomic or genetic ones may contribute to high levels of accumulation of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
154
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(160 citation statements)
references
References 139 publications
6
154
0
Order By: Relevance
“…Highly increased ZEN concentrations at elevated CO2, however, could not be associated with the number of dead spikelets. Plant resistance to Fusarium and mycotoxin production is a highly complex mechanism, including also antioxidant secondary metabolites, which can be toxic to the fungi, participate in cell wall reinforcement as well as interfere with toxin biosynthesis (Atanasova-Penichon et al 2016). Fast activation of the antioxidant defence system was also matched with better resistance levels of plants (Khaledi et al 2016, Spanic et al 2017.…”
Section: Don and Zen Concentrations Of The Grains In Response To Elevmentioning
confidence: 85%
“…Highly increased ZEN concentrations at elevated CO2, however, could not be associated with the number of dead spikelets. Plant resistance to Fusarium and mycotoxin production is a highly complex mechanism, including also antioxidant secondary metabolites, which can be toxic to the fungi, participate in cell wall reinforcement as well as interfere with toxin biosynthesis (Atanasova-Penichon et al 2016). Fast activation of the antioxidant defence system was also matched with better resistance levels of plants (Khaledi et al 2016, Spanic et al 2017.…”
Section: Don and Zen Concentrations Of The Grains In Response To Elevmentioning
confidence: 85%
“…Phenylalanine is the direct precursor of cinnamic acid and p-coumaric acid, respectively. Interestingly, cinnamic acid and p-coumaric acid are potent inhibitors of trichothecene biosynthesis (Atanasova-Penichon et al, 2016). The activation of the phenylpropanoid pathway is well described during pathogen infection (Divon & Fluhr, 2007;H€ uckelhoven, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest cell‐wall lignification to be an important component of FHB resistance in moderately resistant wheat genotypes and have concluded that FTIR‐based markers can be used to differentiate genotypes (Atanasova‐Penichon et al, ; Gunnaiah & Kushalappa, ; Lahlali et al, ; Lahlali et al, ). In contrast, our study did not find any consistent results for some important bipolymeric compounds such as cellulose, pectin, and xylan.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, histopathology studies were mostly aimed at understanding the host–pathogen interaction and pathogen infection processes (Anderson, ; Arthur, ; Atanasoff, ; Brown et al, ; Jansen et al, ; Kang & Buchenauer, ; Miller et al, ; Pugh et al, ; Ribichich et al, ). More recent studies have focussed on metabolomics, proteome, or gene expression profiling of the host–pathogen interaction (Gunnaiah & Kushalappa, ; Atanasova‐Penichon, Barreau, & Richard‐Forget, ; reviewed in Kazan, Gardiner, & Manners, ; Shah et al, ). A large number of candidate genes in resistant cultivars are associated with the phenotypic expression and temporal and spatial profiling of the genes.…”
Section: Introductionmentioning
confidence: 99%